ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK SYARIAH DAN BANK KONVENSIONAL: PERSPEKTIF KONTRIBUSI AKTIVA BERSIH OPERASI - Fitriyah, Lailatul; Yuliana, Rita (Jurnal Akuntansi, Audit, dan Aset, 2019)
This research is used to measure the comparison of the financial performance of Islamic banks andconventional banks in general and specifically. The objects used in this research are all Islamic Banks(BI) and Conventional Banks (BC) in Indonesia for the period 2013-2017. Research variables use theReturn on Investment (ROI) ratio to measure financial performance in general and the Return NetOperating Asset ratio (RNOA) to measure financial performance specifically. The test equipment usedwas the average difference test (Independent Sample T-test). The results of this study indicate that theROI ratio of Islamic banks is superior to conventional banks. Whereas in the RNOA ratio, conventionalbanks are superior to Islamic banks.